Надання електронних послуг у контексті електронної ідентифікації в Україні - Лаба, Оксана (Видавництво Львівської політехніки, 2017)
The basic methods of electronic identification are described. The practical aspects of the implementation of electronic identification in electronic information resources of public authorities are analyzed. The main trends in the development of electronic identification in Ukraine are identified.
Keywords: електронна ідентифікація; BANK ID; електронні інформаційні ресурси; електронний цифровий підпис